Tinjauan Sistematik Literatur: Trade-Off antara Specialization dan Flexibility dalam Ship Design serta Dampaknya terhadap Economic Performance dan Operational Utilization - Rahmiatin, Sitti; Mokodompit, Eliyanti Agus (Pusat Riset dan Inovasi Nasional, 2026)
It is a challenge for the maritime industry to optimize ship design in order to enhance economic performance and operational utilization by balancing specialization and flexibility. According to a comprehensive analysis of the literature conducted between 2020 and 2025, specialist ships like bulk and container carriers can reach cost reductions of about 30–40% with utilization rates of about 85–92%, although they are also susceptible to fluctuations in the market. However, flexible vessels, also known as multifunctional vessels, have greater capital and operational expenditures but offer stable revenue and good utilization. These disparities can be reduced by implementing digital technologies like artificial intelligence, digital twins, and machine learning, which will improve economic performance by 15% to 20% while reducing fuel and maintenance expenses. As a result, ship owners' risk tolerance, operational needs, and long-term vision all influence investment choices. In order to facilitate better decision-making in the evolution of the maritime industry period, this study proposes a comprehensive strategy combined with the four primary variables.